A Határőrvidék alakulatainak betagolódása az osztrák-magyar haderő területi struktúrájába 1872-1883 - Suba, János (Közép-Európai Közlemények, 2013)
Military frontiers were arranged in the southern part of Hungary, next to the Ottoman Empire, after 1699 and 1718. The territory legally belonged to Hungary, in fact it was directed by the Council of War in Vienna. The Austrian military law referred to every inhabitant in the area. The military frontiers performed the task of defending the borders. The territory of the military frontiers consisted of 14 regimental districts and each regiment contained 12 company districts. The borderguard troops took part in every war of the Austrian Empire. As the Ottoman Empire has been driven back on the Balkans, the military frontiers completed its task. Its territory became integrated in the administration of Hungary and Croatia, while its military forces partly in the common military forces, partly in the Hungarian army. Therecruiting districts were also designated.